Combinations of (lipo)glycopeptides with β-lactams against MRSA: susceptibility insights. (26th June 2020) - Kebriaei, Razieh; Rice, Seth A; Singh, Nivedita B; Stamper, Kyle C; Nguyen, Logan; Sheikh, Zain; Rybak, Michael J
Abstract: Background: Increasing application of vancomycin due to the high prevalence of MRSA infections has led to the emergence of vancomycin intermediate-resistant Staphylococcus aureus (VISA) and heterogeneous VISA (hVISA). Consequently, the need for alternative therapies that target MRSA has become evident. Objectives: To evaluate the synergy between (lipo)glycopeptides (LGP/GPs) (vancomycin, teicoplanin, telavancin, dalbavancin and oritavancin) and β-lactams (ceftaroline, cefepime, cefazolin and oxacillin) against MRSA, hVISA, VISA and daptomycin non-susceptible (DNS) phenotypes. Methods: Twenty randomly selected clinical MRSA strains (i.e. 5 MRSA, 5 hVISA, 5 VISA and 5 DNS) were assessed versus LGP/GPs alone and LGP/GPs in combination with β-lactams for MICs. Although verification of antibiotic potency against bacterial strains is assessed by the microbroth dilution (MBD) MIC method recommended by the CLSI, some antibiotics need modified assay conditions in order to demonstrate their optimal activity. Results: Addition of β-lactams reduced MIC values of LGP/GPs against all strains (up to 160-fold reduction). In general, LGPs (dalbavancin, oritavancin and telavancin) were more active (significant differences in MIC values, up to 8-fold) compared with vancomycin and teicoplanin. The majority of these combinations were bactericidal and superior to any single agent. Conclusions: This report has examined the susceptibility patterns of LGP/GPs and their combination with β-lactams. Of interest, the impact of susceptibility tests (in terms of MIC plates and their surface area) on the synergistic activity in 24 h time–kill experiments was apparent for LGPs. Further clinical research is required to investigate synergy with LGP/GPs and β-lactams against these Staphylococcus strains.